RANCANG BANGUN PEMBERIAN PAKAN DAN PENGATURAN PH AIR OTOMATIS PADA TAMBAK UDANG BERBASIS ATMEGA32 - Mulkan Iskandar Nasution; Risma Khoiriah Simbolon (Universitas Negeri Medan, 2020)
ABSTRACTIt has been done the research on the design of automatic feeding and adjusting the pH of water in shrimp pond based on atmega32. By using atmega32 microcontroller as a system design. Water pH setting uses a peristaltic pump to drain water which containing buffer solutions. Ultrasonic sensors detects feed supplies. If the feed is running low, then the buzzer will ring. The servo motor is used to open the lid on the feed container so that the more servos move the more feed is given to shrimp. This device could also be used to measure the temperature of water for shrimp pond by using DS18B20 temperature sensor. The results showed that the pH sensor testing obtained good results because the device was able to maintain the pH value as needed. If the pH of water in the pond is more than 8.5 or less than 6.5 then the pump will become active and work to distributive water mixed with the buffer solution into the pond. The feed container uses an ultrasonic sensor to read the distance if the feed is running low inside the container. If the sensor measures a distance of more than 4 cm then the buzzer will inactive but if the distance is less than 4 cm then the buzzer will active and beep. At the time of feeding, the servo motor will move to open the cover of the feed container with a single movement of 0.7 grams of feed given. In order for the feed to spread, the fans are used for spreading of the feed. Keywords : Atmega32, Feed, pH sensor, Temperature Sensor, and Ultrasonic Sensor.